2022
DOI: 10.5130/cjlg.vi27.7935
|View full text |Cite
|
Sign up to set email alerts
|

Decentralisation and local governance in Nigeria: issues, challenges and prospects

Abstract: Nigeria is a decentralised federation with a three-tier system of federal, state and local governments. Arising from this decentralisation, local governments are empowered to exercise certain powers and responsibilities in areas relating to grassroots development, local democracy and service delivery. Hence, local government plays a pivotal role in local governance. This paper synthesises studies on local government in Nigeria within the broader context of decentralisation and local governance. It takes a care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…He further argued that the continued appointment of 30% of the assembly members and the nomination of the MMDEs defeated the non-partisan nature of the assemblies at the local level. In a study conducted by Ogunnubi [ 76 ] in Nigeria, the findings suggest that central government controlled local government through staff recruitment, allocation, promotion and remuneration are the major challenges hindering the effective participation of the citizenry as local allegiance is shifted to the center.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…He further argued that the continued appointment of 30% of the assembly members and the nomination of the MMDEs defeated the non-partisan nature of the assemblies at the local level. In a study conducted by Ogunnubi [ 76 ] in Nigeria, the findings suggest that central government controlled local government through staff recruitment, allocation, promotion and remuneration are the major challenges hindering the effective participation of the citizenry as local allegiance is shifted to the center.…”
Section: Resultsmentioning
confidence: 99%
“…Mwesigwa [ 77 ] summed it up well by stating that the challenges associated with popular participation were those relating to the central government's reluctance to cede power and resources to the local level. Series of studies conducted in Nigeria including those by Ogunnubi [ 76 ] and Anayochukwu et al [ 78 ] revealed that financial resources to local government were woefully inadequate for effective running of local government including the promotion of effective citizen participation in local development planning. In addition, Ogunnubi [ 76 ] stated that there were unnecessary and undue central government control and influences over financial allocations of the local government authorities.…”
Section: Resultsmentioning
confidence: 99%
“…While discussing the gaps in local governance, Ogunnubi (2022) expresses that institutional inefficiency, limited room for discretion, insufficient financial openness, incomplete decentralization in both political and administrative aspects, and corruption are some of the numerous challenges in governance. Challenges of governance in Nepal include inadequate accountability, limited responsiveness and transparency, widespread corruption, noninclusive governance, diminished credibility of public institutions, excessive politicization in governance practices, and insufficient innovation in governance (Baral & K.C., 2023).…”
Section: Introductionmentioning
confidence: 99%